GERIATRICS THROUGH AYURVEDA: A REVIEW - Krishna Namdeo, Kadam; Viraj Vilas, Jadhav (International Journal of Ayurveda and Pharma Research, 2015)
The World population of the elderly is increasing significantly and by the year 2050, adults older than 65 years will comprise 1/5th of the global population. In India 3.8% of the population are older than 65 years of the age. According to an estimate the likely number of people in India by 2016 will be around 113 million. Approximately 1 in 10,000 persons in developed countries lives beyond 100 yrs. Present day statistics indicate that under ideal socio-economic conditions mean age of death is not far from 85 yrs. Women have life-span about 5yrs longer than men and about 5 times as many women as men reach 100 yrs. Three factors that affect the life-span are: Heredity, Diet and Ionizing Radiation. Changes with age are universal, intrinsic, progressive and deleterious. All cells engage in four basic major activities-Production of energy needed for vital cell processes, synthesis of proteins, both structural and enzymatic, maintenance of chemical and osmotic homeostasis, reproduction or replication. Ayurveda has a focused branch of medicine called Rasayana (Rejuvenation) which exclusively deals with the problems related to ageing and methods to counter the same. Geriatrics or Jara Chikitsa or Rasayana in Ayurveda is a method to control/slow down/arrest the ageing process in the human being during the degenerative phase in ones life. For present article author has collected many references regarding how to enhance concept of Geriatrics through principles of Ayurveda with respect to disorders in Jara avastha and Rasayana therapy.